2014
DOI: 10.3945/ajcn.114.090605
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in African Americans: dose-response

Abstract: Nut consumption decreases risk of some diseasesDear Sir:We read with interest the recent meta-analysis of nut consumption and risk of cardiovascular disease and type 2 diabetes (1). The authors reported that high consumption of nuts decreased the risk of coronary artery disease and hypertension but not stroke or type 2 diabetes. A meta-analysis in this field is very important because the results have been inconsistent, and the authors clarified this association. However, 2 of the studies (2, 3) might not be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Controversy on the outcome of vitamin D on bone health, fragility fractures and falls can be explained, at least in part, by differences between: supplemental doses; duration of supplementation; ethnic/racial target populations; baseline vitamin D status ( 21 30 ). Furthermore, interpretation in terms of inadequacy/adequacy of serum 25OHD baseline levels and-or intervention-induced changes in response to supplemental vitamin D can differ when related to the concept of the “Estimated Average Requirement (EAR) or to the “Recommended Dietary Allowance (RDA)”, as well as to the method of assessment ( 31 , 32 ). The notion of inadequacy/ adequacy of the vitamin D status is still much more difficult to delineate when putative extraskeletal effects are considered.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy on the outcome of vitamin D on bone health, fragility fractures and falls can be explained, at least in part, by differences between: supplemental doses; duration of supplementation; ethnic/racial target populations; baseline vitamin D status ( 21 30 ). Furthermore, interpretation in terms of inadequacy/adequacy of serum 25OHD baseline levels and-or intervention-induced changes in response to supplemental vitamin D can differ when related to the concept of the “Estimated Average Requirement (EAR) or to the “Recommended Dietary Allowance (RDA)”, as well as to the method of assessment ( 31 , 32 ). The notion of inadequacy/ adequacy of the vitamin D status is still much more difficult to delineate when putative extraskeletal effects are considered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, at a median intake equal to the AR, 50% of a population group will have intakes that may be inadequate for the chosen criterion of nutritional status [ 5 ]. Some of the panellists in the IOM DRI committee have suggested that given the inherent variability, the appropriate approach to achieve a low prevalence of vitamin D inadequacy within a population group—as verified by statistical modelling—is to shift the intake distribution so that most of the population (97.5%) have vitamin D intakes above the EAR of 10 μg/day (not above the RDA) [ 21 ].…”
Section: How Food-based Approaches Together With New Drv May Help mentioning
confidence: 99%
“…Moving beyond the comparative studies, results from a large, four-arm (placebo and 25, 50 and 100 µg/d) randomised trial in African American adults reported a vitamin D intake of 41 µg/d was needed to reach the RDA-associated 25(OH)D threshold of 50 nmol/l (74) , but this study has been criticised in terms of its design and interpretation. Firstly, Brannon et al (2) have disputed the need for such high doses of vitamin D, stating the aim should not be to achieve a population intake equivalent to the RDA, as to do so would result in a shift in the population distribution of 25(OH)D to values that exceed the upper limit where the risk of hypercalcaemia increases sharply. Brannon et al claim that dose-response trials should focus on the estimations of the EAR, for which dietary requirements refer to the needs of the population rather than the individual (2) .…”
Section: Adultsmentioning
confidence: 99%
“…Firstly, Brannon et al (2) have disputed the need for such high doses of vitamin D, stating the aim should not be to achieve a population intake equivalent to the RDA, as to do so would result in a shift in the population distribution of 25(OH)D to values that exceed the upper limit where the risk of hypercalcaemia increases sharply. Brannon et al claim that dose-response trials should focus on the estimations of the EAR, for which dietary requirements refer to the needs of the population rather than the individual (2) . However, unlike many nutrients, estimation of both an EAR and RDA is possible through dose-response trials with vitamin D, as 25(OH)D is a valid biomarker of exposure and conditions of minimal UVB availability are achieved at high latitude in winter.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation